Analysis of performance and roasting quality in a rotary cylinder-type coffee roasting machine - Pakaya, Isran Mohamad; Radi, Radi; Purwantana, Bambang; Dharmawan, Agus (Department of Agricultural Products Technology, Mulawarman University, 2025)
The roasting process significantly impacts coffee's aroma and flavor profile, making it crucial in coffee processing. This study developed a rotating drum coffee roasting machine at laboratory scale with 2.0 - 2.5 kg batch capacity. Heat is provided by an LPG-powered pressure cooker burner. The research aimed to evaluate machine performance and assess roasted coffee quality. The roasting process is classified into light, medium, and dark levels. Tests show roasting temperatures from 192°C to 225°C, with times between 12 and 17 min. Moisture content of roasted coffee ranges from 2% to 7%, lower than SNI-7465:2008 standards. The motor requires 23.34 watts of electrical power to operate. Energy consumption for light and medium roasts is 4708.93 kJ, while dark roast needs 9417.86 kJ. Roasted coffee uniformity exceeds 90% at all roasting levels. The weight loss does not exceed 20%. The performance test results indicate the machine's suitability for small-scale coffee industries or laboratories to improve roasting efficiency. Future improvements should focus on better temperature and time control for enhanced flavor profiling.